Prolegomena to an internalist meta-ethics - Zhang, K (2021)
A classic split in meta-ethics concerns whether there are mind-independent normative truths. Those like Derek Parfit and T. M. Scanlon maintain that there are such truths; others like Christine Korsgaard and Sharon Street reject that claim. This BPhil dissertation takes the latter approach to meta-ethics, which it calls an internalist meta-ethics, as its starting point. It then develops such an internalist meta-ethics in several ways. In Chapter 1, it discusses the difference between externalist and internalist accounts of the normative domain, and it motivates an exploration of the prospects of an internalist account. In Chapter 2, it asks which normative attitudes should be taken to ground normative truths for the internalist. It contends that much of the existing literature is mistaken in thinking that we must find one attitude that exhaustively grounds normative truths, and it argues that the broader notions of normative endorsement and rejection, which can run through different attitudes, are the proper grounds of normative truths. Finally, in Chapter 3, it asks whether internalism has the resources to meet prominent substantive objections that concern prudential goodness. Advancing two new internalist arguments, it contends that all rational agents, in virtue of continuing to make endorsements and rejections in the present, are committed to the conclusion that they have reason to pursue their strongest counterfactual endorsements – a result which can provide the internalist a promising rejoinder to the substantive objections in question. The conclusion of these explorations will be a cautious optimism about the prospects of internalism.